ANALISIS KINERJA KARYAWAN SELAMA PANDEMI COVID - 19 PADA PT LINTASARTA DI JAKARTA PUSAT - Achmad Sulistyono (KOLONI, 2022)
During the COVID - 19 pandemic during the Large-Scale Social Restrictions (PSBB), companies are required to be able to build performance by utilizing effective conditions and resources. One form of adaptation that was carried out during the pandemic was work from home (WFH). This research wants to see how company management manages Human Resources (HR) assets during the COVID - 19 pandemic by implementing the WFH mode. The method used in this study is a qualitative approach through observation and interviews. The results in this study are that during the COVID - 19 pandemic, company management had to prepare new methods and requirements to keep work operations going. The challenge experienced by management, especially the leaders, is in controlling their workers directly to provide directions and tasks so they have to go online which causes a lack of feeling because it is different from face-to-face meetings, as well as the lack of working hours so they have to be able to manage time properly. Keyword: Work Performance, Pandemic, Work From Home